Visualizing the Unseen: Hibriditas Video Eksperimental dan Data Sains Lingkungan untuk Advokasi Publik - Ario Wibisono; Nabila Huringiin (Institut Seni Indonesia Yogyakarta, 2026)
Visualizing the Unseen: The Hybridity of Experimental Video and Environmental Scientific Data for Public Advocacy. This article departs from the problem that quantitative environmental data is often too abstract to stimulate public engagement, thus requiring new approaches in science communication. This study investigates how the integration of scientific data and experimental video techniques—such as datamoshing, time-lapse, and augmented reality—can create stronger environmental narratives for public advocacy. Using a practice-based research methodology, the article analyzes the case study of the River of Plastic project, a video installation that visualizes microplastic pollution data. The findings reveal the process of translating quantitative data into specific aesthetic video parameters, in which pollution concentration determines the intensity of visual glitches, scene speed, and color shifts, transforming invisible data into an immediate and emotional sensory experience. The study concludes that this hybridity not only produces artwork but also functions as a strategic innovation tool in science communication, proven effective in raising public awareness, sparking discussion, and strengthening evidence-based policy advocacy arguments.